Preliminary investigation of the in vitro anti-Helicobacter pylori activity of Triphala - Zhu, Zhixiang; Zou, Yuanjing; Ou, Ling; Chen, Meiyun; Pang, Yujiang; Li, Hui; Hao, Yajie; Su, Bingmei; Lai, Yuqian; Zhang, Liping; Jia, Junwei; Wei, Ruixia; et al. (Frontiers in Pharmacology, 2024)
Abstract：Triphala, is a composite of three individual botanical drug herbs: Terminalia chebula, Terminalia bellirica, and Emblica officinalis. It exhibits properties such as heat-clearing, anti-inflammatory, anti-fatigue, antioxidant, and antibacterial effects, making it extensively utilized in India and Tibet. It has been found to exhibit inhibitory effects on Helicobacter pylori (H. pylori); however, further comprehensive research is still needed to elucidate its specific antibacterial mechanism. The present study investigates the in vitro antibacterial activity and antibacterial mechanism of Triphala against H. pylori. The research findings indicate that Triphala exhibits a minimum inhibitory concentration of 80-320 μg/mL against both standard and clinical strains of Helicobacter pylori. Triphala exerts its anti-Helicobacter pylori effect by perturbing the microstructure of H. pylori, downregulating adhesion-associated genes (alpA, alpB, babA), urease-related genes (ureA, ureB, ureE, ureF), and flagellar genes (flaA, flaB); inhibiting bacterial adhesion, biofilm formation, urease activity inhibition as well as CagA protein expression. These findings suggest that Triphala exerts inhibitory effects on Helicobacter pylori activity through multiple mechanisms, underscoring its potential as a new drug for the prevention and treatment of Helicobacter pylori infection.